Peningkatan Kemampuan Insya’ Muwajjah Melalui Media Papan Susun Kalimat pada Santri di Madrasah Diniyyah Assunniyyah Kencong Jember - Riris Fikriyatun Nashihah; Imam Wahyudi; Asep Maulana (Mantiqu Tayr: Journal of Arabic Language, 2024)
Arabic is one of the most widely used languages ​​in the world, especially among Muslims, because it is the language of the Qur'an and hadith. In learning Arabic, there are five skills that must be mastered by students, one of which is writing skills (maharah al-kitabah), which includes insya' muwajjah skills, namely guided composition or composing sentences. However, in practice, many students face obstacles such as boredom, difficulty in composing sentences, and lack of innovation in learning. To overcome this, this study aims to improve the insya' muwajjah skills of class 1 high school students at Madrasah Diniyyah Assunniyyah Kencong Jember by using sentence board media. This study uses a descriptive qualitative method, with data collection through observation, interviews, documentation, and written tests. Data analysis is carried out by reducing data, presenting data, and drawing conclusions, as well as triangulating data sources. The results of the study indicate that the use of sentence board media can increase students' interest in learning, reduce boredom, and make it easier for them to compose sentences in Arabic. This media is also effective in helping teachers deliver materials in a more interesting and interactive way. Thus, it can be concluded that the sentence board media is effective in improving the insya' muwajjah abilities of students and making the learning process more interesting and enjoyable.